Blood flow restriction training - Lorenz, D. S.; Bailey, L.; Wilk, K. E.; Mangine, R. E.; Head, P.; Grindstaff, T. L.; Morrison, S. (Journal of Athletic Training, 2021)
Muscle weakness and atrophy are common impairments after musculoskeletal injury. Blood flow restriction (BFR) training offers the ability to mitigate weakness and atrophy without overloading healing tissues. It appears to be a safe and effective approach to therapeutic exercise in sports medicine environments. This approach requires consideration of a wide range of factors, and the purpose of our article is to provide insights into proposed mechanisms of effectiveness, safety considerations, application guidelines, and clinical recommendations for BFR training after musculoskeletal injury. Whereas training with higher loads produces the most substantial increases in strength and hypertrophy, BFR training appears to be a reasonable option for bridging earlier phases of rehabilitation when higher loads may not be tolerated by the patient and later stages that are consistent with return to sport.